Kualitas Program Pelayanan Kesehatan Gratis (Universal Coverage) Di Badan Layanan Umum Rumah Sakit Umum Pusat Prof. Dr. R. D. Kandou Manado (Studi Kasus Di Instalasi Rumah Inap E). - Lumempow, Gideon Gabriel; Rares, Joyce; Pombengi, Jericho (Sam Ratulangi University, 2014)
As written on roadmap of policy achievement, in 2012-2013 every region in Indonesia had a duty to developed health assurance to assured every citizen to achieve an universal health coverage. Therefore, every region should made an universal health coverage programme which is used ABPD as a fund resource. Government of Manado has issued a free universal health coverage programme for every citizen with ID Card or Family Card for the submission. This research focus on service quality of BLU Prof. Kandou Hospital of Manado as a care-taker if the service that have given appropriate to Prof. Kandou Hospital’s standart procedure. Research Method: This research using qualitative-descriptive approaching method in depth interview to 7 respondent, observation and files investigation. This research using additional instrument i.e. questionnaire, recorder and writing equipment. Result: According to prime service quality points those are transparency, accountability, conditional, rights equivalence, balance and duty, the service implementation of universal health coverage programme at BLU Prof. Kandou Hospital of Manado is going well. The obstacle was in application submission procedure in district or representative office of health ministry that sometimes had problem and the DPHO doesn’t appropriate to doctor’s advice. Conclution: BLU Prof. Kandou Hospital of Manado has given a good quality service of free universal health coverage programme according to the research that have done in IRINA E. Keywords: Service Quality, Public Service, BLU Prof. Kandou Hospital of Manado as a care taker, Universal Coverage Manado.